Cohesive Devices for Enhancing Reading Comprehension among EFL Students in Nepal - Pitambar Paudel (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
Reading is a key to developing other language skills and aspects of language. However, most of the EFL students are unable to comprehend the reading texts adequately and completely. Against this backdrop, the purpose of this classroom action research is to examine the role of using cohesive devices in improving students' reading comprehension. The study was conducted in a five-week intervention experiment for a class of 40 non-English majors at a Nepalese public university. The data were collected from tests (pre-test, progress-test, and post-test), and interviews. The data were analysed using quantitative statistics (mean, standard deviation, and T-test), and the data from the interview were analysed textually. The overall results revealed that knowledge and the use of cohesive devices led to significant improvements in students’ reading comprehension. The findings suggest that the study's intervention the "use of cohesive devices "was effective in improving students' reading comprehension. Thus, students are to be encouraged to be aware of understanding and using cohesive devices for increasing their reading comprehension. This implies that teachers should teach cohesive devices and guide students in identifying and using them to improve reading comprehension.